Altered endotoxin responsiveness in healthy children with Down syndrome - Dean Huggard (BMC Immunology, 2018)
Abstract Background Down syndrome (DS) is the most common syndromic immunodeficiency with an increased risk of infection, mortality from sepsis, and autoinflammation. Innate immune function is altered in DS and therefore we examined responses in CD11b and Toll like receptor 4 (TLR-4), which are important immune cell surface markers upregulated in response to Lipopolysaccharide (LPS) endotoxin, and the immunomodulator melatonin. Neutrophil and monocyte responses to LPS and melatonin in children with Down syndrome (DS) who were clinically stable were compared to age-matched controls. Whole blood was incubated with LPS and melatonin and the relative expression of CD11b and TLR-4 evaluated by flow cytometry. Results Children with DS had an increased response to LPS in neutrophils and intermediate monocytes, while also having elevated TLR-4 expression on non-classical monocytes compared to controls at baseline. Melatonin reduced CD11b expression on neutrophils, total monocytes, both classical and intermediate sub-types, in children with DS and controls. Conclusion Melatonin could represent a useful clinical adjunct in the treatment of sepsis as an immunomodulator. Children with DS had increased LPS responses which may contribute to the more adverse outcomes seen in sepsis.